Autonomic modulation at rest and in response to postural change in adolescents with Duchenne muscular dystrophy: A cross-sectional study - Rodrigues, Mariana Viana [UNESP]; Stoco-Oliveira, Mileide Cristina [UNESP]; da Silva, Talita Dias; Ferreira, Celso; Valente, Heloisa Balotari [UNESP]; Vanzella, Laís Manata [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (My University, 2021)
Background: Analysis of autonomic modulation after postural change may inform the prognosis and guide treatment in different populations. However, this has been insufficiently explored among adolescents with Duchenne muscular dystrophy (DMD). Objective: To investigate autonomic modulation at rest and in response to an active sitting test (AST) among adolescents with DMD. Methods: Fifty-nine adolescents were included in the study and divided into two groups: 1) DMD group: adolescents diagnosed with DMD; 2) control group (CG): healthy adolescents. Participants' weight and height were assessed. Lower limb function, motor limitations and functional abilities of the participants in the DMD group were classified using the Vignos scale, Egen classification and motor function measurement, respectively. The following variables were assessed before, during and after AST: systolic blood pressure (SBP), diastolic blood pressure (DBP), respiratory rate (f), oxygen saturation and heart rate (HR). To analyze the autonomic modulation, the HR was recorded beat-by-beat. Heart rate variability (HRV) indices were calculated in the time and frequency domains. Results: Differences in relation to groups were observed for all HRV indices, except LF/HF, oxygen saturation, HR and f (p < 0.05). Differences in relation to time and the interaction effect between group and time were observed for RMSSD, SD1, SD2, SD1/SD2, LFms2 and LFnu, HFun, SBP and DBP (p < 0.05). Differences in relation to time were also observed for the indice SDNN, FC and f (p < 0.05). Conclusions: Performing the AST promoted reduced autonomic modulation and increased SBP, DBP and HR in adolescents with DMD.
Keywords: Autonomic nervous system diseases; Duchenne; Heart rate; Muscular dystrophy; Posture